Mamma, pappa - och sedan barn? - Om bilden av föräldrarna i relation till principen om barnets bästa - Laxén,Iara (2017)
The purpose of this essay is to examine how the issue of a suitable parent and the sex of the parent is described and influences in custody battles and how this relates to the principle of what is best for the child. This has been done by analyzing, examining and discussing how the parents are described by social services and courts. In the essay a classic legal method and a discourse analysis have been used. I have done interviews with civil servants at different social service offices and have studied legal cases. A gender law studies perspective and the principle of what is best for the child have been applied. There is no presumption for or against joint custody in Swedish law. The question of joint or sole custody should always be decided in each specific case. With joint custody, the parents have a shared responsibility for the child and its affairs. With sole custody, the responsibility fall on the parent in question. If none of the parents are suitable to take care of the child a court can rule that a specially ordained care giver shall be granted custody. The principle of what is best for the child should be decisive at every decision regarding custody. It should be specially considered if risks exist that are dangerous for the child and that the child has a need to have a close and good relationships with both of its parents. The will of the child should be considered, in relation to the age and maturity of the child. The child needs to be taken care of and protected as well as to have its integrity respected by both of its parents. 2017, the Swedish government has received an official inquiry that suggest that the conception of what is best for the child should be even more central. Two examples are that the ability of the parents to put the child’s interest before their own conflict should specially be considered and that the child has a right to express his or her opinion. A suitable parent has been found to be someone who see the child, can describe the child and its needs. A suitable parent have preferably been living in an equal household, so that both parents can see the child’s needs and the number of conflicts can reduce, but an equal parenthood is not necessarily a suitable parenthood. Children should be held out of the conflict of the parents and a suitable parent makes sure of that. To satisfy the emotional needs of ones children is important. So is taking responsibility for ones child and home. Differences can be seen in how the parents are described, but they are not so big that it affects the rulings. What is best for the child is guiding.
Keywords: familjerätt; barnets bästa; vårdnadsmål; genusrättsvetenskap